PURSUING POINTS OF CONVERGENCE AMONG RELIGIOUS COMMUNITIES - Arfan Muhamad; Abdul Hadi Sukmana (Tahiro : Journal of Peace and Religious Mederation, 2025)
Religious community should be understood as a sign God of power on human beings. diversity has become the fact that could not be denied.  Because of every human being has the distinction of education, environmental, socio-cultural, ethnic, language and different experience in his live. These differences should be viewed from ontology of theological.  Religions like a candle in the night, every human being would feel worried if there are no candles behind. All of the candles will provide illumination to mankind in the dark of his life in this world. Every religion must have universal values ??that should be plucked from the religious community. Messages from all prophetic (holy men) should be guidance of human beings to achieve happiness dan blackness.  This article, will be describe of universal values ??in religious community.